Acute haemorrhagic conjunctivitis caused by coxsackievirus A24 (variant), in Belém, Pará, Brazil, 1987 - Santos, Elisabeth de O.; Macedo, Olinda; Gomes, Maria de Lourdes C.; Nakauth, Célia Maria (Revista do Instituto de Medicina Tropical de São Paulo, 1989)
An epidemic of acute haemorrhagic conjunctivitis in Belém, Pará, Brazil, was investigated. From 83 patients, 73 samples of virus was isolated in cultures of HEP-2 cells from conjunctival swab and throat swab. The virus isolates were identified in Centers for Disease Control, Atlanta, Georgia, USA, as an antigenic variant of coxsackievirus A24. Neutralization Test was done on 56 paired serum samples, using entero virus type 70 (E V70) and virus isolates. Serological conversions for virus isolates were found in 57% (32 patients).